2010
DOI: 10.1124/jpet.109.165332
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Multidrug Resistance-Associated Protein 4 in Efflux Transport of Prostaglandin E2 across Mouse Blood-Brain Barrier and Its Inhibition by Intravenous Administration of Cephalosporins

Abstract: Prostaglandin E 2 (PGE 2 ) acts as a modulator of synaptic signaling and excitability in the brain. Because PGE 2 is barely inactivated enzymatically in adult brain, its brain level is considered to be controlled by efflux transport across the bloodbrain barrier (BBB). The purpose of the present study was to clarify the efflux transport of PGE 2 at the BBB and the interaction of various drugs with this process. [ 3 H]PGE 2 was eliminated from brain across the BBB with a half-life of 16.3 min, and the eliminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…Efflux systems at the BBB have been characterized for compounds whose accumulation in the CNS would lead to neuronal damage such as amyloid b (Shibata et al, 2000), prostaglandin E 2 (Akanuma et al, 2010), and interleukin-2 (Banks et al, 2004). We observed that an efflux system also exists for CCL11.…”
Section: Discussionmentioning
confidence: 69%
“…Efflux systems at the BBB have been characterized for compounds whose accumulation in the CNS would lead to neuronal damage such as amyloid b (Shibata et al, 2000), prostaglandin E 2 (Akanuma et al, 2010), and interleukin-2 (Banks et al, 2004). We observed that an efflux system also exists for CCL11.…”
Section: Discussionmentioning
confidence: 69%
“…The present study indicates that indomethacin and diclofenac inhibit OAT3-mediated PGD 2 transport (Table 2). Furthermore, we have found that cefmetazole, cefazolin, ceftriaxone, and cefotaxime, administered intravenously to mice, inhibit [ 3 H]PGE 2 efflux transport from the brain across the blood-brain barrier most likely because of the inhibition of MRP4 (Akanuma et al, 2010). Thus, the inhibitory effect on the PGT-and OAT3-mediated PGD 2 transport should be taken into consideration in the development of new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The transporters were shown to allow prostaglandin outflow from the brain tissue by exerting their actions at the polarized CNS-blood barrier. It was also demonstrated that this process is slowed at the transporter level by β-lactam antibiotics like cefmetazole and cefazolin or during inflammation (Akanuma et al, 2010;Akanuma et al, 2011;Tachikawa et al, 2012). Prostaglandin influx transporters are found in both the solute carrier organic anion (Slco) transporter family and the cation (Slc) transporter family.…”
Section: Pge2 Transportersmentioning
confidence: 99%
“…In the same study, another contradiction discussed by the authors was the early drop of PGE2 in CSF despite remaining high levels of COX-2 and mPGES-1. This as yet unsolved problem might have been answered in paper II by the up-regulation of the prostaglandin transporters in the barrier that by their suggested functions and cellular membrane localizations would contribute to the brain PGE2 clearance (Akanuma et al, 2010;Tachikawa et al, 2012).…”
Section: Brain Pge2 As a Mediator Of Fever At The Preoptic Regionmentioning
confidence: 99%
See 1 more Smart Citation